SPECIAL OPERATION OF THE CENTRAL INTELLIGENCE DIRECTORATE OF THE UNITED STATES OF AMERICA “AERODYNAMICS” AND THE SPLIT IN THE FOREIGN UNITS OF THE ORGANIZATION OF UKRAINIAN NATIONALISTS IN 1954 - SYCH , Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose is to do the research on the impact of the US CIA special operation “Aerodynamics” on the split in the OUN Foreign Units in 1954. The research methodology is based on adherence to the principles of historicism, objectivity, and scientificity using specific historical, comparative historical, problem chronological, and structural systemic methods. The scientific novelty of the article consists in the fact that for the first time, based on the declassified CIA documents, the OUN archives, domestic archives, and foreign printed sources, there has been analysed the influence of the CIA on the activities of the Ukrainian emigration nationalist organizations of the OUN Foreign Units and Foreign Representation of the Ukrainian Supreme Liberation Council. Conclusions. In the context of the Cold War aggravation, the CIA studied the activities of Eastern European émigré groups for the purpose of cooperation and among the Ukrainians identified the Ukrainian Supreme Liberation Council (UHVR) as such. The cooperation began in 1948 under the code name “Aerodynamics” and lasted until 1990. The first stage of the operation was the penetration of CIA agents into Ukraine, and after 1954 it was carried out in the form of cooperation with the Research and Publishing Association “Prolog”. In 1948, at the Second Extraordinary Conference of the OUN Foreign Units, the first stage of internal discussion was completed, and the participants of the opposition, based on Foreign Representation of the Ukrainian Supreme Liberation Council, voluntarily resigned from their mandates as members of the Ukrainian Supreme Liberation Council and the OUN Foreign Units. The offer of cooperation, financial and material support received from the CIA changed their behavior, they announced the withdrawal of their resignation and stated that they would continue their activities independently. After this, the internal conflict in the OUN Foreign Units got a new momentum. In 1948 – 1954, cooperating with Foreign Representation of the Ukrainian Supreme Liberation Council, the CIA made efforts to discredit its opponents. The CIA demanded from the British intelligence MI6 to abandon cooperation with S. Bandera and the OUN Foreign Units, and among the leadership of the Ukrainian underground, the document “Political Position of the United States Government” was distributed prepared by the CIA employees, which expressed support for the Foreign Representation of the Ukrainian Supreme Liberation Council and condemned the activities of S. Bandera and the OUN Foreign Units. Such actions also contributed to the aggravation of the internal conflict in the OUN Foreign Units, which ended in a split in 1954. Key words: US CIA, special operation “Aerodynamics”, the OUN Foreign Units, Foreign Representation of the Ukrainian Supreme Liberation Council, Research and Publishing Association “Prolog”.